EVALUATION OF RE-USED HPTLC PLATE FOR QUALITATIVE AND QUANTITATIVE ANALYSIS - Lestyo Wulandari (Indonesian Journal of Chemistry, 2006)
The eficiency chromatography of HPTLC plate is better than conventional TLC plate but it more expensive. Due to the higher price of HPTLC plate compare to conventional TLC plate, the application of ";re-used"; HPTLC plate has been tested. After being used for analyzing samples, the plates were developed again with the mobile phase, then dried for 60 min before using for the next measurement. The qualitative chromatography profile showed that ";re-used"; HPTLC plate has less contaminant than new HPTLC plate and the RSD of the precision quantitative testing of the plates reused  three times showed a value > 2%.